Travellers' Perception Of Quality Of Local Tour Attendant Service At Keraton Kasepuhan Cirebon - Dian Fitriyana; Sudiana Wachyudi; Mintahul Maula (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
Kasepuhan Palace in Cirebon, West Java, is a cultural tourist destination that has extraordinary history and cultural riches. As one of the oldest palaces in Indonesia, this place attracts many tourists looking for an authentic historical and cultural experience. The quality of service provided by local tour guides at Kasepuhan Palace plays an important role in the tourist experience. Understanding tourists' perceptions of the quality of local tour guide services is an important step in maintaining and increasing the attractiveness of this cultural destination in the eyes of visitors. This research uses a quantitative approach, in collecting data obtained through direct observation, questionnaires, interviews and document recording of tourists who visit the Kasepuhan Palace, Cirebon. Determining the number of samples in this study used purposive sampling, sample selection was based on certain criteria, the service quality measurement aspects analyzed were reliability, responsiveness, assurance, empathy, tangible. This research also considers factors that influence tourists' perceptions of frame of reference & field of experience. This research also discusses the problems that arise at the Kasepuhan Palace in Cirebon due to the imbalance between the limited number of tour guides and the significant number of tourist visits. The results of this research provide an overview of the quality of local tour guide services that influence tourists' perceptions, and how these perceptions influence tourist satisfaction during a visit to the Kasepuhan Palace.